Development of an attendance system based on cloud / fog computing - Younis, Mohamed I.; Younis, Manal F.; Abed, Marwa M.; Alsewari, Abdulrahman A. (University of Baghdad-College of Science, 2020)
Given the high importance of attendance for university students, upon which the possibility of keeping or losing their places in the course is based, it is essential to replace the inefficient manual method of attendance recording with a more efficient one. To handle this problem, technology must be introduced into this process. This paper aims to propose an automatic attendance system based on passive Radio Frequency Identification (RFID), fog, and cloud computing technologies (AASCF). The system has three sides. The first one, which is the Client-side; works on collecting the attendance data then sending a copy from it. The second side, which is the Server-side, works on calculating an absence ratio of all the students during the course. The third side is the Fog-server. Data sent by the client-side reaches to the Fog-server which, in turn, sends data to the cloud at the end of the of working time at the university. This paper also reviews the state-of-the-art automatic attendance systems and shows the merits and demerits for each approach by providing a checklist comparison. Unlike the previous works, the proposed system protects data from wasting and ensures its arrival to the cloud even in cases of connection losing or device crashing, which is the contribution of this paper.